Residue and distribution of drip irrigation and spray application of two diamide pesticides in corn and dietary risk assessment for different consumer groups. (11th June 2022) - Li, Xianjia; Sun, Zheng; Yan, Tiantian; Li, Yuan; Zhang, Xue; Liu, Miaojiao; Lin, Yigang; Zhang, Zhixiang; Xu, Hanhong
Abstract: BACKGROUND: As the use of diamide insecticides on corn continues to increase, there is growing concern about their residue levels on corn and dietary risks to populations. In this study, the distribution, dispersion and transfer efficiency of two diamide insecticides (tetrachlorantraniliprole (TCAP) and cyantraniliprole (CNAP)) in different parts of corn and soil were investigated in a 1‐year field trial in Guangzhou and Lanzhou using two different application methods – spray and drip irrigation, respectively – and the dietary risk of the insecticides to different consumer populations was assessed under the two application methods. RESULTS: The results showed that drip irrigation had a longer persistence period than spraying, and there was a hysteresis in the absorption distribution of the agent in different parts of corn, which was gradually transferred to the leaves after absorption from the roots. The average TE1 (transfer efficiency) and TE2 were 0.230–0.261 and 1.749–1.851 for TCAP and 0.168–0.187 and 2.363–2.815 for CNAP, respectively. At corn harvest, both TCAP and CNAP were below detectable levels in soil and corn. For different consumer populations, hazard quotients ranged from 0.001 to 0.066 for TCAP and from 0.003 to 0.568 for CNAP – both well below 100%. CONCLUSION: This study indicates that TCAP and CNAP applied by spray or drip irrigation are safe for long‐term risk of human intake and also provides guidance for the use of both insecticides in agricultural production to control corn pests, especially in arid and semi‐arid areas. © 2022 Society of Chemical Industry.